Arabic Teacher Creativity Survey during the Pandemic Period in Elementary Schools - Maykoski Chew; Thilo Spurdle; Pierquin Mathieu (Yayasan Adra Karima Hubbi, 2023)
During the current Covid-19 pandemic, the Government stipulated that face-to-face learning should not be carried out, so learning activities were replaced with an online system. This study aims to determine the Creativity of Arabic teachers during a pandemic in elementary schools. This type of research uses quantitative methods. Data was collected through a survey, in which the researcher gave the same systematic or structured questions to many people via Google. The results of this study describe the Creativity of Arabic language teachers during the pandemic in elementary schools, especially at MI Darul Iman Muara Lembu. Based on a research survey, the Arabic teacher at the school used the media or the Whatsapp application to support and assist the process of learning activities during this pandemic. So, the Whatsapp application can help and make it easier for students to access learning materials sent by the teacher. Also, students can ask questions via chat if they need help understanding the material the teacher explains, with the guidance of parents or other families.